Systemic knowledge and the V-model. (19th July 2005) - Sheffield, Jim
A simple but surprisingly useful system of inquiry is outlined and applied to elicit and validate systemic knowledge. Systemic knowledge is the holistic understanding of interpersonal expectations or norms, the technical system, and the relationships between the two. General systems concepts such as hierarchy and intentionality are employed to generate a new V-model that incorporates the familiar concepts of "top down" design and "bottom up" implementation. The V-model validates systemic knowledge by testing the strength of a chain of evidence that emerges from the application of design principles to a practical knowledge management problem.